2005
DOI: 10.1128/cmr.18.3.556-569.2005
|View full text |Cite
|
Sign up to set email alerts
|

Novel Perspectives on Mucormycosis: Pathophysiology, Presentation, and Management

Abstract: Mucormycosis is a life-threatening fungal infection that occurs in immunocompromised patients. These infections are becoming increasingly common, yet survival remains very poor. A greater understanding of the pathogenesis of the disease may lead to future therapies. For example, it is now clear that iron metabolism plays a central role in regulating mucormycosis infections and that deferoxamine predisposes patients to mucormycosis by inappropriately supplying the fungus with iron. These findings raise the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
1,614
1
42

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,305 publications
(1,676 citation statements)
references
References 168 publications
(238 reference statements)
19
1,614
1
42
Order By: Relevance
“…Nevertheless, even with aggressive therapy, the rate of mortality is often above 50% (4, 6). It is clear that new strategies for the treatment of zygomycosis are urgently needed.Posaconazole (POS) is a new broad-spectrum triazole with activity against many filamentous fungal pathogens, including zygomycetes (3,8,11,13,14). Experimental infection models and clinical data showed that POS might be useful for the treatment of zygomycosis (3,11,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, even with aggressive therapy, the rate of mortality is often above 50% (4, 6). It is clear that new strategies for the treatment of zygomycosis are urgently needed.Posaconazole (POS) is a new broad-spectrum triazole with activity against many filamentous fungal pathogens, including zygomycetes (3,8,11,13,14). Experimental infection models and clinical data showed that POS might be useful for the treatment of zygomycosis (3,11,14).…”
mentioning
confidence: 99%
“…The zygomycetes most commonly identified as etiologic agents of human diseases are Rhizopus species, Rhizomucor species, Mucor species, and Absidia species (13). The invasive forms of zygomycosis cause angioinvasion, followed by progressive, necrotic, and generally fatal infections in immunocompromised hosts, such as diabetic patients with ketoacidosis, neutropenic patients, patients taking corticosteroids, and subjects with burns or iron overload (4,6,7,12,13). The standard therapy for these life-threatening infections consists of removal of the predisposing factors, widespread surgical debridement, and high doses of intravenous amphotericin B (AMB) (13).…”
mentioning
confidence: 99%
“…It is Fig. 4 After the infection was controlled with systemic antifungal therapy, she underwent final debridement and split skin graft on the wound as shown also now established that iron metabolism plays a central role and iron chelation using deferiprone is a promising novel therapeutic strategy for refractory mucormycosis [14].…”
Section: Discussionmentioning
confidence: 98%
“…1 With fall in blood pH, there is an increased release of iron from transferrin that enhances hyphal growth. 2 Chakrabarti et al, 2006 in their retrospective study of 178 cases of invasive mucormycosis (54.5% rhino-orbito-cerebral, 14.6% cutaneous, 9.0% disseminated, 8.4% gastrointestinal, 6.7% each of renal and pulmonary mucormycosis) showed that 73.6% of cases had uncontrolled diabetes mellitus. 3 Our patient was also a case of diabetes with poor compliance that lead to uncontrolled hyperglycemia and ketoacidosis.…”
Section: Discussionmentioning
confidence: 99%